Morphology and morphometry support a single species in the Leucheria cerberoana species complex (Asteraceae, Nassauvieae) - Apodaca, María José; Palacio, Facundo X.; Katinas, Liliana (Phytotaxa, 2021)
Leucheria (Asteraceae, Mutisioideae, Nassauvieae) has been traditionally defined as a South American genus with 49 species. In the context of an ongoing revision of the genus, we observed that 10 Chilean species (Leucheria cerberoana, L. cumingii, L. glabriuscula, L. glandulosa, L. menana, L. multiflora, L. oligocephala, L. senecioides, L. tenuis, L. tomentosa) were morphologically difficult to distinguish from each other. This group of species, called here the Leucheria cerberoana complex, shares the following features that differ from the other species of Leucheria: marginal florets and fruits of the capitulum tightly enclosed by the outer and the inner phyllaries, synaptospermy and a dimorphic pappus. Here, we test the current morphological circumscription of these 10 species on the basis of the analysis of 171 specimens. We carried out multivariate analyses (Principal Coordinate Analysis and K-means) based on 16 external morphological characters. We also examined anatomically the underground organs because these species were distinguished from each other by their annual or perennial life cycle. We found that all the specimens analyzed have underground organs with secondary growth and thus there are not annual species in this group. Our results showed that there are no morphological gaps among specimens supporting the hypothesis of a single species. It is proposed here to synonymize these species under the name Leucheria tomentosa (Lessing) Crisci. With this change, the number of species of Leucheria is reduced from 49 to 40.